Guidance counselling and social studies education: impetus for national rebirth in the wake of social milieu in Nigeria - Tinja, R. Maina; Tijani, O. A.; Ishaq, Y. (Kashere Journal of Education, 2023)
This paper discusses Guidance and counselling; and Social Studies Education in relationship to national rebirth and nation building viz their roles in sensitizing the Nigerian students on the need for behaviour modification and general attitudinal restructuring for the main purpose of nation building and national transformation. In the context of this, the paper is centred on the concept of guidance and Counselling, Social Studies Education national rebirth, nation building, behavioural factors that negate nation building and the place of Guidance Counselling and Social Studies as well as the various strategies applicable to the two subject areas in preparing the learners nation building. On the basis of the issues discussed, the paper made recommendations that Government at all levels should be committed to education development through the employment of qualified counsellors and social Studies educators for effective citizenship orientation in Nigeria to achieve the desired result, provision of office accommodation and other working tools to the counsellors, adequate funding of education by government at all levels, etc.